Use of K-Means Cluster to Analyze Electrical Properties and Soil Texture Melon Plantation - Nelsa Indah Artamevia; Mimin Iryanti; Yuyu Rachmat Tayubi (Lambung Mangkurat University Press, 2023)
West Kalimantan is a province in Indonesia that has 1.73 hectares of peatland. In utilizing peat soil, it is necessary to know several indicators, such as electrical conductivity and soil texture, to see whether or not it is suitable for plantation land. This study examines the relationship between electrical conductivity and soil texture supported by the K-Means Cluster statistical method on peat melon plantations in The village of Rasau Jaya, West Kalimantan. Electrical conductivity measurements were carried out using a conductivity meter, soil texture classes were determined using the USDA (United States Department of Agriculture) classification method, and clustering was used the K-Means Cluster statistical method. Besides that, the physical characteristics of the soil were observed visually using the Munsell Soil Color Chartbook. The research showed that melon plantation soil has two layers with straight-line delineation. The first layer has a range of electrical conductivity values of 0.14 dS/m, has a clay texture, and has a color code of 10 YR 2/1. The second layer has a range of electrical conductivity values of 0.07 dS/m, has a sandy loam texture, and has a color code of 10 YR 2/1